2021
DOI: 10.3390/molecules26092773
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Quality, Antioxidant Capacity, and Digestibility of Chickpea (Cicer arietinum L. cv Blanoro) Stored under N2 and CO2 Atmospheres

Abstract: The aim of this work was to monitor the quality, antioxidant capacity and digestibility of chickpea exposed to different modified atmospheres. Chickpea quality (proximal analysis, color, texture, and water absorption) and the antioxidant capacity of free, conjugated, and bound phenol fractions obtained from raw and cooked chickpea, were determined. Cooked chickpea was exposed to N2 and CO2 atmospheres for 0, 25, and 50 days, and the antioxidant capacity was analyzed by DPPH (2,2′-diphenyl-1-picrylhydrazyl), AB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 68 publications
1
12
0
Order By: Relevance
“…Similar trends of fluctuation in ACW and ACL were reported during the second and third months of storage in another study on antioxidant changes in red cabbages [78]. The results from the green lentil snack bar in the first and second months of observation are in agreement with the ABTS test (p > 0.05), which also detects the presence of hydrophilic and lipophilic antioxidants in the sample [79]. The ACW and ACL values of the samples might be influenced by several factors such as the method of maceration (water or methanol extraction) [80], food processing, as well as storage condition (temperature and duration) [78].…”
Section: Total Phenolic Compound and Antioxidant Analysissupporting
confidence: 83%
“…Similar trends of fluctuation in ACW and ACL were reported during the second and third months of storage in another study on antioxidant changes in red cabbages [78]. The results from the green lentil snack bar in the first and second months of observation are in agreement with the ABTS test (p > 0.05), which also detects the presence of hydrophilic and lipophilic antioxidants in the sample [79]. The ACW and ACL values of the samples might be influenced by several factors such as the method of maceration (water or methanol extraction) [80], food processing, as well as storage condition (temperature and duration) [78].…”
Section: Total Phenolic Compound and Antioxidant Analysissupporting
confidence: 83%
“…Furthermore, a study explained that each radical shows different affinities although in the same sample. ABTS has a higher affinity with hydrophilic, lipophilic compounds, and hydrogen atom donors, while DPPH has a higher affinity for lipophilic compounds and less affinity for compounds containing aromatic rings with only -OH groups [ 80 ]. Floegel et al [ 81 ] also compared the antioxidative activity of various food products measured by ABTS and DPPH assays to the USDA ORAC database and reported that the ABTS assay reflects the antioxidant activity in various food products (particularly plant-based foods) better than DPPH assay.…”
Section: Resultsmentioning
confidence: 99%
“…The supernatants were combined and were evaporated in a rotary evaporator (RE301, Yamato, Santa Clara, CA, USA) at 45–50 °C. Then, the sample was resuspended in a final volume of 2 mL with methanol (Perez‐Perez et al., 2021). This extract was used for the quantification of total bound phenols and antioxidant capacity, whereas the sediment was lyophilised and used for fermentation tests.…”
Section: Methodsmentioning
confidence: 99%
“…Ultra performance liquid chromatography–mass spectrometry (UPLC‐MS) analysis of PC was performed on a liquid chromatograph (Acquity 2690, Waters Corp, Milford, MA, USA) coupled to mass spectrometry SQ Detector 2 simple quadrupole (Waters Corp) as previously reported by Perez‐Perez et al. (2021). Phenol‐Explorer 3.6. was used to identify PC and for verification by mass spectrometry from 100 to 750 m z −1 in negative ionisation mode with a cone voltage of 30 kV and a desolvation temperature of 400 °C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation